Antecedents of positive and negative intergroup contact: Evidence from a diary study. (8th March 2022) - Prati, Francesca; Schaefer, Sarina J.; Hewstone, Miles; Christ, Oliver
Abstract : In our current globalised, multicultural world, understanding antecedents of reciprocal interactions between native people and people of immigrant background is a major issue, because intergroup contact plays a crucial role in building inclusive societies. In this vein, using daily diary data, we examined the relation between the number of daily positive and negative interactions of White British majority ( N = 744) and Asian British minority people ( N = 582) with members of the respective outgroup, with RWA, SDO, perceived ingroup norms, neighbourhood diversity and contextual deprivation. Results showed that for the majority group, ingroup norms in favour of intergroup contact were positively associated with positive intergroup encounters, whereas Right Wing Authoritarianism (RWA) was positively associated with negative intergroup contact. Neighbourhood diversity was positively associated with positive and negative intergroup encounters. Moreover, RWA moderated the relationship between neighbourhood diversity and both positive and negative contact of White British people. For the minority group, ingroup norms were positively associated with positive intergroup contact, and the relationship between ingroup norms and negative contact was moderated by SDO. Overall, different factors affect positive and negative intergroup contact of majority and minority groups. We discuss the implications of the findings for future research and interventions.